2010
DOI: 10.1162/jocn.2010.21416
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Control and the Frontal Eye Fields

Abstract: Inhibitory control mechanisms are important in a range of behaviors to prevent execution of motor acts which, having been planned, are no longer necessary. Ready examples of this can be seen in a range of sports, such as cricket and baseball, where the choice between execution or inhibition of a bat swing must be made in a brief time interval. The role of the FEFs, an area typically described in relation to eye movement functions but also involved in visual processes, was investigated in an inhibitory control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 48 publications
2
35
1
Order By: Relevance
“…If a participant's CRT on any trial in any of the subsequent sessions was two standard deviations longer than their mean CRT from this block, they would receive visual feedback saying "You did not press the button fast enough" to serve as a reminder to press the button as soon as the arrow appeared. This procedure has been demonstrated to effectively limit the strategy of intentionally slow responses that participants sometimes use to avoid errors ( [16][17][18]). …”
Section: Stop-signal Paradigmmentioning
confidence: 99%
“…If a participant's CRT on any trial in any of the subsequent sessions was two standard deviations longer than their mean CRT from this block, they would receive visual feedback saying "You did not press the button fast enough" to serve as a reminder to press the button as soon as the arrow appeared. This procedure has been demonstrated to effectively limit the strategy of intentionally slow responses that participants sometimes use to avoid errors ( [16][17][18]). …”
Section: Stop-signal Paradigmmentioning
confidence: 99%
“…When performing a manual inhibitory control task, the signal from the retina is projected from the visual areas to brain regions that are related to inhibitory control, such as frontal eye fields (FEF, Curtis et al, 2005;Hanes and Schall, 1996;Muggleton et al, 2010), supplementary eye fields (SEF, Isoda and Hikosaka, 2007;Stuphorn et al, 2000;Stuphorn and Schall, 2006), and anterior cingulate cortex (ACC, Chevrier et al, 2007;Ito et al, 2003). Information converges at the primary motor cortex (M1), which executes motor commands by transmitting them to the spinal cord and muscles.…”
Section: The Neural Correlates Of Inhibitory Controlmentioning
confidence: 99%
“…Consistent with this notion, brain regions underlying inhibitory control comprise frontal eye fields (FEFs, Curtis, Cole, Rao, & D'Esposito, 2005;Muggleton, Chen, Tzeng, Hung, & Juan, 2010), pre-supplementary motor cortex (pre-SMA, Isoda & Hikosaka, 2007), and supplementary eye fields (SEFs, Stuphorn & Schall, 2006;Stuphorn, Taylor, & Schall, 2000), while performance is monitored by the anterior cingulate cortex (ACC, Chevrier, Noseworthy, & Schachar, 2007;Ito, Stuphorn, Brown, & Schall, 2003). Hsu et al (2011) found, in a go/no-go task, that anodal tDCS applied over the pre-SMA (Fz vs left cheek; 1.5 mA for 10 min, pair of 4 Â 4 cm 2 electrodes) improved efficiency of inhibitory control, while cathodal tDCS showed a tendency towards impaired inhibitory control.…”
Section: Executive Attentionmentioning
confidence: 73%